Altitude isotope effects in Mediterranean high-relief terrains: a correction method to utilize stream water data. Issue 9 (4th July 2021) - Hemmerle, H.; van Geldern, R.; Juhlke, T. R.; Huneau, F.; Garel, E.; Santoni, S.; Barth, J. A. C.
ABSTRACT: Quantification of the isotope altitude effect from precipitation allows the identification of recharge altitudes in high-relief areas. However, steep terrains frequently limit the use of this precipitation-based approach. Perennial rivers often provide easy, year-round access for water sampling. However, in high-relief regions rivers may not adequately represent regional precipitation isotope patterns because they integrate isotope signals along their course. This prevents the calculation of an altitudinal isotope gradient from river water samples alone. We present a study that shows how a river-based sampling approach served to determine the altitude effect. Replacing the original sample site altitude with the mean upstream catchment elevation as calculated from a digital elevation model allowed us to establish a plausible altitude isotope effect from stream water. The correction approach was verified independently using precipitation isotope data. This approach can potentially be transferred to other regions where precipitation sampling at various elevations is difficult to determine.